Complement C3d conjugation to anthrax protective antigen promotes a rapid, sustained, and protective antibody response. - Ravi V Kolla; Suresh Chintalapati; Mojgan Sabet; Eugenio Santelli; Robert C Liddington; Michael David; Joshua Fierer; Donald Guiney; Robert C Rickert (PLoS ONE, 2007)
B. anthracis is the causative agent of anthrax. Pathogenesis is primarily mediated through the exotoxins lethal factor and edema factor, which bind protective antigen (PA) to gain entry into the host cell. The current anthrax vaccine (AVA, Biothrax) consists of aluminum-adsorbed cell-free filtrates of unencapsulated B. anthracis, wherein PA is thought to be the principle target of neutralization. In this study, we evaluated the efficacy of the natural adjuvant, C3d, versus alum in eliciting an anti-PA humoral response and found that C3d conjugation to PA and emulsion in incomplete Freund's adjuvant (IFA) imparted superior protection from anthrax challenge relative to PA in IFA or PA adsorbed to alum. Relative to alum-PA, immunization of mice with C3d-PA/IFA augmented both the onset and sustained production of PA-specific antibodies, including neutralizing antibodies to the receptor-binding portion (domain 4) of PA. C3d-PA/IFA was efficacious when administered either i.p. or s.c., and in adolescent mice lacking a fully mature B cell compartment. Induction of PA-specific antibodies by C3d-PA/IFA correlated with increased efficiency of germinal center formation and plasma cell generation. Importantly, C3d-PA immunization effectively protected mice from intranasal challenge with B. anthracis spores, and was approximately 10-fold more effective than alum-PA immunization or PA/IFA based on dose challenge. These data suggest that incorporation of C3d as an adjuvant may overcome shortcomings of the currently licensed aluminum-based vaccine, and may confer protection in the early days following acute anthrax exposure.